2022
DOI: 10.1155/2022/8045401
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness of Life Cycle Cost Theory-Based Large Medical Equipment

Abstract: The purpose of this study is to use the life cycle cost theory to analyze the efficiency of large medical equipment in hospitals, so as to implement life cycle cost (LCC) management and solve the current problems in hospitals. The analysis model of cost benefit of large medical equipment is established, and the cost-effectiveness of 4 large medical equipment between 2019 and 2021 is investigated and analyzed. In terms of the data in each information system of hospitals, the utilization of large medical equipme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This hidden cost that is seldom taken into consideration that leads to increase in operational cost of hospitals and also indirectly leads to rising costs of medical diagnosis and care. 10 The total life of medical equipment includes procurement, usage, maintenance, and depreciation of the equipment, which are closely interrelated. From the perspective of hospital procurement system, the above-mentioned links belong to different departments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hidden cost that is seldom taken into consideration that leads to increase in operational cost of hospitals and also indirectly leads to rising costs of medical diagnosis and care. 10 The total life of medical equipment includes procurement, usage, maintenance, and depreciation of the equipment, which are closely interrelated. From the perspective of hospital procurement system, the above-mentioned links belong to different departments.…”
Section: Introductionmentioning
confidence: 99%
“…With the surge in management requirements, expected quality of medical care, and scientific research ability of hospitals, expensive medical equipment are frequently purchased and utilized in the daily operation systems of hospitals to greatly promote the improvement of administration, delivery of healthcare, and scientific research levels of hospitals. 10 Besides, the in-depth use of large medical equipment in daily hospital diagnosis and treatment and the benefits it creates are the main sources of income of hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, reducing the occurrence of waste means that the costs incurred do not exceed the budgeted costs. With reasonable cost control, the company's operational activities can run smoothly (Chang et al, 2022;Shamayleh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%